Effect of Zinc Smelter Effluent and Soil Amendments on Metallic Cations Build-up in Soil and Yield of Crop Plants - Totawat, K L (Annals of Arid Zone, 2016)
A pot culture study was undertaken in a sandy loam soil using five dilutions of Zinc Smelter’s treated effluent with well water for irrigation and five soil amendment treatments to raise maize, sorghum, wheat and barley. The cliy matter production of maize, sorghum and barley significantly decreased when undiluted effluent was used for irrigation. However, effluent when diluted with well water and used for irrigation has improved the city matter yield. Incorporation of phospho-gypsum has increased the dry matter yield of maize and barley and lowered the level of available Fe, Mn and Zn build-up in soil.